Increased Costs and Health Care Utilization Associated with Delay in Diagnosis of ACL Injuries. Issue 7 (31st July 2020) - Cook, Sara; Byrnes, Thomas; Hagen, Mia; Gee, Albert; Kweon, Christopher; Slattery, Casey
Objectives: Anterior cruciate ligament (ACL) injuries can be difficult to diagnose, especially among providers with limited musculoskeletal training. Early and accurate diagnosis of ACL injuries is important for initiating proper treatment and limiting inefficient or costly healthcare utilization. We hypothesized that a delayed diagnosis in patients sustaining ACL injuries would result in treatment that is more costly and utilizes more healthcare resource compared to patients diagnosed without delay. Methods: A large national private insurance database (Truven MarketScan) was utilized to identify all patients aged 10-63 years-old diagnosed with an ACL tear from 2011 through 2015. Patients with a possible delay in diagnosis were determined via a database search for the most commonly assigned alternative knee-related diagnosis codes found in patients who were later diagnosed with an ACL tear. Patients were stratified into three groups according to time from non-specific knee diagnosis code to ACL diagnosis: 1) no delay (0 days), short delay (1-30 days) and long delay (>30 days). Subsequent cost and healthcare utilization data including physical therapy, medication use, and number of clinic visits were collected for a period of one-year after initial presentation with an ACL tear or knee-related diagnosis. Results: A search from 2011 through 2015 identified 87, 435 patients meeting inclusion criteria that were diagnosed with an ACL injury. There were 24.1% of patients diagnosed at initial presentation whereas 43.5% were diagnosed between one day and 30 days. There were 38.2% of patients that were treated without surgery and had the lowest total cost regardless of delay in diagnosis (Table 1). ACL reconstruction combined with other knee procedures had the highest total cost, particularly with a longer delay in diagnosis. Each day of delay in diagnosis was three times more costly in the non-surgical (additional 27.06 cost per day of delay) versus the surgical groups (8.09 cost per day of delay). Conclusions: A timely diagnosis of ACL injuries is associated with a lower cost of treatment and less visits to healthcare providers. Non-operative injuries may benefit the most from a timely diagnosis given the high additional cost per day of diagnosis delay. In order to further decrease the burden on the healthcare system, future studies should assess methods than can decrease delays in diagnosis while measuring cost and utilization differences as well as outcomes after ACL tears.